Fried Chocolate Bread with Panir Flour untuk Tumbuh Kembang Anak Pada Pondok Pesantren Wihdatul Ulum Di Desa Bontokassi Kecamatan Parangloe Kabupaten Gowa - Nurwahyuni Nurwahyuni; Suriyanti Suriyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Indonesia has a large population, especially children. Chocolate is almost liked by all groups. In addition to being delicious, chocolate also has various benefits forthe body, from improving mood to maintaining heart health. Starting from children, teenagers, to adults, many like to eat chocolate. In addition to its distinctive and delicious taste, chocolate also has health benefits. Chocolate is a processed cocoa bean that is roasted, ground, then formed into a liquid, paste, or in block form. Dark chocolate or dark chocolate contains antioxidants, vitamins, and minerals that are good for the body. Now there are many chocolates that are processed with the addition of sugar, milk, and so on. Instead of getting the health benefits of chocolate, consuming this type of chocolate is dangerous for health. Therefore, if you want to feel the benefits of chocolate, consume dark chocolate without adding excess sugar. because this product has an affordable price and has great benefits.